Prevalence of subtle menstrual disturbances in female endurance athletes of different performance levels: The FENDURA Project - De Martin Topranin, V.; Taylor, M.; Engseth, T. P.; Noordhof, D. A. (Book of Abstracts. 4th Nordic Winter Sports Conference "Performance in snow sports: Translating science into practice" 3rd-4th October, 2022, Mid Sweden University, Campus Östersund, Sweden, 2022)
Aim To describe the rate of occurrence of subtle menstrual disturbances (MD) in female endurance athletes and the prevalence of MDs across different performance levels.